The nervous and prenervous roles of serotonin in Echinococcus spp. - Camicia, Federico (2013)
Serotonin (5-hydroxytryptamine, 5-HT) is an important neuroactive and morphogenetic molecule in several metazoan phyla, including flatworms. Serotoninergic nervous system studies are incomplete and 5-HT function/s are unknown in Echinococcus spp., the flatworm parasites that cause hydatid disease. In the present work, we searched for genes of the serotoninergic pathway and performed immunocytochemical and functional analyses of 5-HT in Echinococcus spp. Bioinformatic analysis using the recently available Echinococcus multilocularis and Echinococcus granulosus genomes suggests the presence of genes encoding enzymes, receptors and transporters participating in 5-HT synthesis, sensing and transport in these parasites. However, some components of the pathway could not be identified, suggesting loss or divergence of parasite homologous genes. The serotoninergic neuroanatomy study performed by confocal scanning laser microscopy on different E. granulosus stages showed an increasing level of complexity when the protoscolex develops towards the adult stage and a progressive diminution when the parasite develops towards the metacestode stage. The role of 5-HT as a neurotransmitter in E. granulosus was evaluated by determining the effect of this substance on protoscolex motility. The addition of 5-HT to protoscoleces induced a significant increase in motility for short time periods. Preincubation with 100 lM citalopram, a known 5-HT transporter inhibitor, abolished the 5-HT-induced increase in motility, indicating that the effect could be mediated by a 5-HT transporter. Incubation of protoscoleces with 5-HT for time periods of several days induced a progressive differentiation towards the metacestode stage. The results indicate that 5-HT could have nervous and prenervous roles during Echinococcus spp. development. Taking into account the important roles of 5-HT in parasite biology and the divergence of 5-HT pathway genes with respect to human counterparts, the serotoninergic system could be considered as an amenable drug target against hydatid disease.